Factors associated with COVID-19 preventive behaviors among taxi drivers in Bangkok - Deesua, Amornrat; Kaewpan, Wonpen; Kalampakorn, Surintorn; Sillabutra, Jutatip (Frontiers in Public Health, 2023)
Objectives This paper aimed to identify factors associated with COVID-19 preventive behaviors among taxi drivers in Bangkok. Methods This cross-sectional study included 401 taxi drivers. Data were analyzed using descriptive statistics. The association between predisposing factors, enabling factors, and reinforcing factors with COVID-19 preventive behaviors was analyzed by using analysis of variance and Pearson's Product Moment Correlation. Multiple linear regression analysis was used to determine the influencing factors in predicting COVID-19 preventive behaviors of taxi drivers. Results The present findings revealed that income adequacy, support from family, co-workers, and healthcare professionals, perceived susceptibility, severity, benefits, barriers, and health motivation, accessibility to personal protective equipment for COVID-19 and preventative measures against COVID-19 from other agencies were associated with good COVID-19 preventive behaviors among taxi-driver in Bangkok during COVID-19 pandemic (R2 = 0.349, p = 0.008). The model could predict 34.9% of variance in COVID-19 preventative behavior among taxi drivers. Conclusion Taxi drivers should be encouraged to engage in appropriate preventive behaviors against COVID-19, emphasizing the individual and organizational levels. There should be a policy by organizations to promote the implementation of COVID-19 safety control standards to ensure safe working conditions. In addition, appropriate welfare benefits should be provided for taxi drivers, such as loans, personal protective equipment, and access to health services to improve COVID-19 preventive behaviors.